Constraints Analysis of Cauliflower Growers in Western Uttar Pradesh - Sunil Kumar, R.N. Yadav and Hari Nandan Prasad, (Indian Journal of Extension Education, 2023)
The study was carried out during the year 2016-2017 in the cauliflower higher production area of WesternUttar Pradesh, Saharanpur region in the district of Saharanpur and Meerut region in district of Hapur overpromising region for cauliflower cultivation. The number of two blocks selected for the study. Mujaffarabadblock in district Saharanpur and Hapur block in district Hapur was purposively selected. The total samplesize was of 160 cauliflower growers for the study. The result of the study depicted the majority of therespondents 51.25 per cent were belonging to lower middle age group ranging 30-45 years. Maximum76.87 per cent respondents were belonged to other backward classes. The majority of the cauliflower growerswere literate. The majority of 71.25 per cent the respondents were belonged to joint family system andinterested for cauliflower growing. The maximum 61.87 per cent respondents of the cauliflower growerswere having either medium size (5-8 members) of the family. The maximum 62.50 per cent respondentswere having mixed houses. Only 80.00 per cent respondents were depending upon agriculture. The maximum43.75 per cent cauliflower growers were having 01-02 ha of land holding small size. Unavailability ofquality chemical at Govt. sale center, lack of knowledge about bio-fertilizers, fluctuation in the prices, lackof Govt. initiative in funding of loans and granting of subsidies problems in remote areas were all the mostconstraints. Highest majority of cauliflower growers were suggesting that availability of inputs at propertime Govt. sale centre and developed government tube well in every villages.